20x+3+10x=13x-3+7x

Simple and best practice solution for 20x+3+10x=13x-3+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20x+3+10x=13x-3+7x equation:



20x+3+10x=13x-3+7x
We move all terms to the left:
20x+3+10x-(13x-3+7x)=0
We add all the numbers together, and all the variables
20x+10x-(20x-3)+3=0
We add all the numbers together, and all the variables
30x-(20x-3)+3=0
We get rid of parentheses
30x-20x+3+3=0
We add all the numbers together, and all the variables
10x+6=0
We move all terms containing x to the left, all other terms to the right
10x=-6
x=-6/10
x=-3/5

See similar equations:

| 4x−2x=20 | | -3r+-27=-35 | | 190=4y^2-6 | | 7(x+3)-11=31 | | (4y+7)+(6y+3)=180 | | 71-w=186 | | x+9−0.8x=5.2x+17−8 | | 295+26+b=360 | | 4(u+3)=-2(5u-4)+6 | | 8x-2+6+2x=x+4+9x | | x/3+29=25 | | -10+2-5x+3x=26 | | -3x=-4x+17 | | 3n-3+5=14 | | x+x+2+x+4-22=x+4 | | 12+2y=126 | | X.2x=-60 | | 2x-8+28=4x+6 | | 1+4x=-3+7x | | 7x+9=4x+75 | | 7s-6s=11 | | -18=5n+8+8n | | 8+3x=3x-6 | | -u-2u-7=8 | | 9x+81=102 | | 182=3n+7(-4n+1) | | 6x+111=13x-7 | | -4+6-6x=38 | | 3-6j=-1-2j+8 | | -11=1+6x+6 | | 9x-27=5x-15 | | 2(4x+9)=-30+40 |

Equations solver categories